Genome Sizes of Nine Insect Species Determined by Flow Cytometry and k-mer Analysis - He, Kang; Lin, Kejian; Wang, Guirong; Li, Fei (Frontiers in Physiology, 2016)
The flow cytometry method was used to estimate the genome sizes of nine agriculturally important insects, including two coleopterans, five hemipterans and two hymenopterans. Among which, the coleopteran Lissorhoptrus oryzophilus had the largest genome of 981 Mb. The average genome size was 504 Mb, suggesting that insects have a moderate-size genome. Compared with the insects in other orders, hymenopterans had small genomes, which were averagely about 200 Mb. We found that the genome sizes of four insect species were different between male and female, showing the organismal complexity of insects. The largest difference occurred in the coconut leaf beetle Brontispa longissima. The male coconut leaf beetle had a 111 Mb larger genome than females, which might be due to the chromosome number difference between the sexes. The results indicated that insect invasiveness was not related to genome size. We also determined the genome sizes of the small brown planthopper Laodelphax striatellus and the parasitic wasp Macrocentrus cingulum using k-mer analysis with Illunima Solexa sequencing data. There were slight differences in the results from the two methods. K-mer analysis indicated that the genome size of L. striatellus was 500-700 Mb and that of M. cingulum was 150 Mb. In all, the genome sizes information presented here should be helpful for designing the genome sequencing strategy when necessary.